2015
DOI: 10.1098/rspb.2014.3027
|View full text |Cite
|
Sign up to set email alerts
|

Hybridization and pre-zygotic reproductive barriers inPlasmodium

Abstract: Sexual reproduction is an obligate step in the life cycle of many parasites, including the causative agents of malaria (Plasmodium). Mixed-species infections are common in nature and consequently, interactions between heterospecific gametes occur. Given the importance of managing gene flow across parasite populations, remarkably little is understood about how reproductive isolation between species is maintained. We use the rodent malaria parasites P. berghei and P. yoelii to investigate the ecology of mixed-sp… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
27
0

Year Published

2016
2016
2021
2021

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 28 publications
(28 citation statements)
references
References 55 publications
1
27
0
Order By: Relevance
“…Gene deletion in P. falciparum and P. berghei and cross-fertilization experiments in rodent species showed an essential role for P48/45 in male, but not female, gametes during fertilization, with production of ookinetes drastically reduced. Motile PbΔP48/45 male gametes were able to adhere to erythrocytes to form exflagellation centers but were unable to attach to females and fertilize, as reported for PbΔ230 (van Dijk et al, 2001, 2010; Ramiro et al, 2015). It is not clear whether the observed phenotype in ΔP48/45 mutants results from the loss of a direct role of P48/45 itself or from the lack of P230 on the plasma membrane (Eksi et al, 2006).…”
Section: 6-cys Proteins In the Sexual Stagessupporting
confidence: 60%
See 2 more Smart Citations
“…Gene deletion in P. falciparum and P. berghei and cross-fertilization experiments in rodent species showed an essential role for P48/45 in male, but not female, gametes during fertilization, with production of ookinetes drastically reduced. Motile PbΔP48/45 male gametes were able to adhere to erythrocytes to form exflagellation centers but were unable to attach to females and fertilize, as reported for PbΔ230 (van Dijk et al, 2001, 2010; Ramiro et al, 2015). It is not clear whether the observed phenotype in ΔP48/45 mutants results from the loss of a direct role of P48/45 itself or from the lack of P230 on the plasma membrane (Eksi et al, 2006).…”
Section: 6-cys Proteins In the Sexual Stagessupporting
confidence: 60%
“…Furthermore, in P. falciparum , exflagellating males are unable to bind to erythrocytes to establish exflagellation centers, which are important for fertilization (Eksi et al, 2006) and, in Plasmodium berghei , ΔP230 male gametes do not recognize female gametes, whereas ΔP230 female gametes have no apparent phenotype (van Dijk et al, 2010). Interestingly, the deletion of either P230 or P48/45 in P. berghei female gametes increased their hybridization with Plasmodium yoelii male gametes (Ramiro et al, 2015). …”
Section: 6-cys Proteins In the Sexual Stagesmentioning
confidence: 99%
See 1 more Smart Citation
“…For example, P. falciparum and P. vivax have 42% amino acid identity. Analysis of P47 sequences from several rodent malaria parasites indicates that P47 is evolving under positive selection [28,29] with exceptionally high ratio of nonsynonymous to synonymous substitutions (dN/dS) in the second domain [28]. …”
Section: P47 Organizationmentioning
confidence: 99%
“…Evidence for hybridizations and introgressions between parasite species is gathering, at least in part in line with improvements in molecular diagnostics and genome sequencing of these organisms. Examples include several causative agents of important NZDS caused by helminths, such as Schistosoma, Fasciola, Ascaris and Trichinella (Schistosoma, Fasciola, Ascaris, and Trichinella; Criscione et al 2007;Dunams-Morel et al 2012;Le et al 2008;Webster et al 2013a), protozoa, such as Plasmodium, Leishmania, Toxoplasma and Trypanosoma (Akopyants et al 2009;Gaunt et al 2003;Grigg et al 2001;Machado and Ayala 2001;Ramiro et al 2015;Rogers et al 2014;Sturm et al 2003), as well as their vectors (King et al 2015). For instance, research on A. lumbricoides and A. suum collected from sympatric human and pig populations in both Guatemala and China found that between 4 and 7% of the roundworms sampled were hybrids.…”
Section: Mixed Species Co-infections and Introgressionsmentioning
confidence: 99%